Waveform interpolation speech coding algorithm at 2.4kbit/s based on wavelet transform - WANG Jing; KUANG Jing-ming; XIE Xiang (Tongxin xuebao)
A waveform interpolation speech coding algorithm at 2.4kbit/s based on wavelet transform was proposed,in which characteristic waveform decomposition and reconstruction is processed using biorthogonal wavelet filters.At the encoder,the alignment operation was removed and the amplitude spectrum is decomposed without phase spectrum.Because of the wavelet compression,only the amplitude spectrum of last layer is transmitted.At the decoder,different scale space is reconstructed separately and random or fixed phase was combined to the spectrum based on voice degree at the last.Additionally,based on the time-variable feature of speech,voiced degree flag of each subframe was introduced to indicate the spectrum selection and quantization.Subjective R-A/B listening tests indicated that the synthesis speech quality of the 2.4kbit/s WT-CWI coding algorithm is better than that of standard 2.4kbit/s MELP coder and FS1016 4.8kbit/s CELP coder and is better than traditional 3.8kbit/s CWI coder.